Who is investing in machine-to-machine communications? - Andres Laya; Vlad-loan Bratu; Jan Markendahl (International Telecommunications Society (ITS), 2013)
Machine-to-Machine (M2M) communications refers to the automate exchange of information between devices for control and monitoring applications. This type of communication is not new since automated systems have been present for more than three decades. However, miniaturization of device's size, reduction of production costs and drop in communication fees (altogether with the massive adoption of real-time access of information in current society) are expanding the set of applications and solutions currently under consideration. The real complexity relies on the fact that M2M is not only an add-on communication solution, like the case of traditional human-centric broadband communications. M2M usually entails a change in the core business of an industry, since the relationship with external partners and the internal tasks can be radically modified In this paper, we anaylise the players involved in M2M communications and how they position themselves in a market which requires them to adjust their traditional business approach. The main question addressed in this work refers to which players are investing in M2M, which is their view and how could their approach affect the current ICT sector? We highlight the dominance and relationship between different actors and also look at barriers that prevent investments, regulations in the area and standardization efforts...
Keywords: 330; Machine-to-Machine communications; M2M; Internet-of-Things; Techno-economic analysis; Service provisioning; Investment